POSISI DAN TRANSFORMASI KISAH-KISAH ALQURAN: (Suatu Pembacaan Terhadap Literatur Ulumul Qur’an dan Kesarjanaan Barat) - Ahmad Tri Muslim HD (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2023)
This article is a reading of the primary literature in the study of the Qur’an in looking at the stories narrated by Qur’an. Likewise, this paper describes how Orientalists interpret the stories of the Qur’an. The purpose of this academic work is to see the methods and approaches of the two scholarships above in interpreting the stories of the Qur’an. In the early literature of Qur’anic studies, it is found that the stories of the Qur’an are not discussed in a special section, but are included in a chapter of tikrar al-Qur’an, Makki wa Madani, or Tanzil al-Qur’an. It differs from the later books on The 'Ulumul Qur’an, which put the discussion of the stories of the Qur’an in separate chapters. However, it is important to emphasize that al-Zarkasyi and al-Suyuti who represent classical scholars have realized the importance of seeing the interlocutors of the stories of the Qur’an and the message conveyed to the first recipients. Meanwhile, western scholarship will find methodological transformation in approaching the stories of the Qur’an along with academic problems regarding the source and truth of the Qur’an.